MODEL PREDIKSI CURAH HUJAN DENGAN REGRESI SPLINES ADAPTIF BERGANDAUSING MULTIVARIATE ADAPTIVE REGRESSION SPLINE TO PREDICT MONTHLY RAINFALL - S. Sutikno; Rizaldi Boer (Agromet, 2004)
Abstract is available in the full text (pdf format)